Single-phased remote on/off control using PIC 16F877 microcontroller / Mohd Suhaimi Sulaiman and Aileen Farida Mohd. Adam - Sulaiman, Mohd Suhaimi; Mohd. Adam, Aileen Farida (2012)
Microcontrollers are very popular in electronics and computer-controlled systems worldwide. This paper presents the control of a microcontroller-based system using the computer and explains comprehensively the hardware and software parts of the microcontroller. Peripheral Interface Controller (PIC) software developed by Microchip (MPASM) is used in programming a PIC microcontroller, and Visual Basic is used in programming the user interface. The developed system showed that the auto-switching mode of transmission could be implemented via the PIC microcontroller and an RS485 transceiver. The PIC microcontroller is chosen to implement the control unit due to its advantages such as high speed, Harvard and Reduced Instruction Set Computer (RISC) architecture, low cost and flexibility for programming. The controller unit used in the mentioned processes is designed. The developed system showed that the Graphical User Interface (GUI) and the microcontroller successfully switched on and off a single-phase lamp via twisted pair cables.